Evaluation of the level of vitamin D3 in the blood serum of patients infected with COVID-19 in Al-Amiriya city - Shannak, Qader Abdullah; Najim, Thaar Mohammed; Madab, Dhamer Ismail (Technium BioChemMed, 2022)
The researchers used 60 samples, 35 of which were infected with the developing corona virus and 25 of which were healthy and disease-free. Their ages ranged from 30 to 55, and the samples were taken from their homes. Al-Amiriya Hospital in An bare Governorate. After that, blood was collected from healthy and sick people and separated by centrifugation. The biochemical variables were Determination, including (CRP ,ferritin, Vit.D3) . In comparison to healthy people, people infected with the developing corona virus had significantly higher levels of C-reactive protein and ferritin in their blood serum, according to the findings of the current study. Also When compared to healthy people, Vit.D3 levels in blood serum of people infected with the developing corona virus were shown to be significantly lower.